(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article is based on the information on the research conducted on the scientific justification of the reproduction of products made on the basis of the melon fruit processing technology in the conditions of the Tashkent region. At the same time, the influence of technological properties and chemical composition of melon on storage properties was studied.